Prawosławie i islam. Dialog św. Cyryla i G rzegorza Palamasa z muzułmanami - Makal, Grzegorz (Elpis, 2014)
The purpose of this study is to present the role of the Holy Fathers in the dialogue between the Orthodox and the Muslims. The first part of the article talks about the mission of St. Cyril in Baghdad Caliphate in historical perspective. It deals with his dialogue with Islam and presents an analysis of the arguments used by both sides. In the second part I talk about the dialogue of St. Gregory Palamas with Muslims in the context of the mission of Cyril, comparing the arguments of both fathers and their attitudes towards the dialogue with Islam. Finally, the theory of the “biblical roots of Europe” is addressed, drawing on the example of the abovementioned Holy Fathers. In the article some excerpts from Palamas’works are published in Polish for the first time.